CONTEXTUAL STORYTELLING TO STRENGTHEN PANCASILA VALUES: A CLASSROOM ACTION RESEARCH STUDY - Sabina Kedeikoto; Mesak Gabou; Bunga Yulin Singgamui; Hendrika Edowai; Antonia Mote; Karola Devita Moyab; Santji Afi Rangkoly (CV. TOTUS TUUS, 2026)
A recurring challenge in Indonesian primary schools is that students often learn Pancasila as memorized principles rather than values practiced in daily interactions. This study investigated whether a storytelling-based learning approach could improve Grade V students’ understanding of Pancasila values at State Elementary School 1 Nabire, Central Papua. The research employed Classroom Action Research (CAR) conducted in two cycles, each comprising planning, action, observation, and reflection, across two meetings per cycle. Participants were 24 fifth-grade students (13 boys, 11 girls). Data were collected through pre-test and post-test measures (KKM = 75) and structured classroom observations of engagement and value-related behaviors, and were analyzed using descriptive quantitative and qualitative techniques. Findings indicated substantial improvement in learning outcomes: the pre-cycle mean score was 63.5 with 25% mastery; after Cycle I, the mean increased to 73.4 with 58.3% mastery; and after Cycle II—which strengthened storytelling using visual media and small-group retelling/discussion—the mean rose to 82.1 with 91.7% mastery. The study concludes that storytelling, particularly when supported by visual aids and participatory discussion, is effective for improving students’ cognitive understanding and classroom engagement in learning Pancasila values. Practically, the approach offers a feasible model for character education in culturally diverse and resource-limited contexts. Future research should test the model with control groups, larger samples, and longer follow-up to assess sustained value internalization and behavioral change.